(untitled) (Aintelia Science Notes, 2024)
Here is the English version, condensed to under 200 words while retaining all technical data, metrics, and case-study details: Industrial microgrids in remote mining environments often operate under weak-grid conditions (SCR < 5), amplifying voltage sags during motor starting and causing variable-frequency drive (VFD) harmonics to exceed the IEEE 519-2022 THD_V limit of 8% at the point of common coupling (PCC). This paper presents an adaptive Static Synchronous Compensator (STATCOM) designed for the 30 kV microgrid at the Compagnie des Phosphates de Gafsa (CPG) mining complex in Tunisia. The system utilizes a three-level neutral-point-clamped (NPC) converter regulated by an adaptive proportional-integral (API) scheme. Controlled by a Lyapunov-stability-based adaptation law, it eliminates the need for offline tuning. MATLAB/Simulink simulations, calibrated with CPG field data, demonstrate that during the direct-on-line starting of a 2.4 MW crusher motor, voltage sags recover from 0.72 p.u. to 0.98 p.u. within 18 ms. Furthermore, THD_V drops from 11.3% to 2.8%, achieving IEEE 519-2022 compliance. Compared to fixed-gain PI STATCOMs, active and reactive power transient overshoot is reduced by 31%, validating the architecture’s performance under weak-grid conditions.